How can food environments support greater fruit and vegetable consumption in Tanzania? A collaborative needs assessment workshop in Arusha - de Bruyn, Julia; Mvungi, Henry; Mwambi, Mercy; Mwombeki, Wiston; Ernest, Zablon; Gordon, Jessica; Meeker, Jessica (CGIAR System Organization, 2024)
On 22 March 2024, the first collaborative needs assessment workshop in Tanzania for the CGIAR Fruit and Vegetables for Sustainable Healthy Diets (FRESH) Initiative was held in Arusha. The workshop was led and hosted by the World Vegetable Center (WorldVeg) Eastern and Southern Africa regional office, with support on the methodology and planning from the Institute of Development Studies (IDS), and was co-hosted with the Arusha Sustainable Food Systems Platform. This group, coordinated by Rikolto, is one of two key stakeholder groups with which the FRESH Initiative has established ongoing connections in Tanzania. The platform was established in 2020, to reflect the broadening of the interests of the Arusha Food Safety Committee, created in 2018, and facilitates multi-stakeholder dialogues to address food system change in Arusha.